AFGHANISTAN: DRUG TRAFFICKING AND REGIONAL SECURITY - KOMISSINA, Irina (CENTRAL ASIA AND THE CAUCASUS, 2005)
It has been almost four years since the Tali-ban regime was overthrown in Afghanistan (an interim government was formed in June 2002) and the country began building a new state with direct assistance from the international antiterrorist coalition. This gave the world community reason to hope that the new authorities, albeit not immediately, would be able to stem the flow of heroin pouring out of the country. After all, in the 1990s it became the leading opium drug producer in the world. Later, when the Taliban came to power, the situation took a dramatic turn for the worse. As follows from a report by the Vienna branch of the U.N. Office on Drugs and Crime—UNODC1 —published in 2003, between 1996 and 1999, the manufacture of drugs in this country increased twofold. And these indices are more than 15-fold higher than during the time a limited contingent of Soviet troops was stationed in Afghanistan.2 In 2000, this state accounted for 70% of the world’s opium production, while Myanma’s “contribution "amounted to 23%, Laos’ to 4%, and Columbia’s to 2%. When the new forces came to power in the country, the situation in this business did not change. Getting the population of a country which had been cultivating opium poppy for more than 25 years to switch gears overnight and start growing agricultural crops proved a rather difficult task. For example, the U.N. Office on Drugs and Crime report published in December 2004 on the results of a survey of the drug situation in Afghanistan noted that this year the area on which opium is grown in the country has increased by two thirds, reaching an unprecedented 131,000 hectares (in 2003, it amounted to 80,000 hectares).3 Precursors for processing opium into heroin and morphine are imported mainly from Pakistan, Thailand, Hong Kong, and India.